The evolutionary history of Afrocanarian blue tits inferred from genomewide SNPs. Issue 1 (3rd December 2014) - Gohli, Jostein; Leder, Erica H.; Garcia‐del‐Rey, Eduardo; Johannessen, Lars Erik; Johnsen, Arild; Laskemoen, Terje; Popp, Magnus; Lifjeld, Jan T.
Abstract A common challenge in phylogenetic reconstruction is to find enough suitable genomic markers to reliably trace splitting events with short internodes. Here, we present phylogenetic analyses based on genomewide single‐nucleotide polymorphisms (SNPs) of an enigmatic avian radiation, the subspecies complex of Afrocanarian blue tits (Cyanistes teneriffae). The two sister species, the Eurasian blue tit (Cyanistes caeruleus) and the azure tit (Cyanistes cyanus), constituted the out‐group. We generated a large data set of SNPs for analysis of population structure and phylogeny. We also adapted our protocol to utilize degraded DNA from old museum skins from Libya. We found strong population structuring that largely confirmed subspecies monophyly and constructed a coalescent‐based phylogeny with full support at all major nodes. The results are consistent with a recent hypothesis that La Palma and Libya are relic populations of an ancient Afrocanarian blue tit, although a small data set for Libya could not resolve its position relative to La Palma. The birds on the eastern islands of Fuerteventura and Lanzarote are similar to those in Morocco. Together they constitute the sister group to the clade containing the other Canary Islands (except La Palma), in which El Hierro is sister to the three central islands. Hence, extant Canary Islands populations seem to originate from multiple independent colonization events. We also found population divergences in a key reproductive trait, viz. sperm length, which may constitute reproductive barriers between certain populations. We recommend a taxonomic revision of this polytypic species, where several subspecies should qualify for species rank.